Macrophage-secreted interleukin-35 regulates cancer cell plasticity to facilitate metastatic colonization - Lee, Chih-Chan; Lin, Jiunn-Chang; Hwang, Wei-Lun; Kuo, Ying-Ju; Chen, Hung-Kai; Tai, Shyh-Kuan; Lin, Chun-Chi; Yang, Muh-Hwa (Nature communications, 2018)
A favorable interplay between cancer cells and the tumor microenvironment (TME) facilitates the outgrowth of metastatic tumors. Because of the distinct initiating processes between primary and metastatic tumors, we investigate the differences in tumor-associated macrophages (TAMs) from primary and metastatic cancers. Here we show that dual expression of M1 and M2 markers is noted in TAMs from primary tumors, whereas predominant expression of M2 markers is shown in metastatic TAMs. At metastatic sites, TAMs secrete interleukin-35 (IL-35) to facilitate metastatic colonization through activation of JAK2–STAT6-GATA3 signaling to reverse epithelial–mesenchymal transition (EMT) in cancer cells. In primary tumors, inflammation-induced EMT upregulates IL12Rβ2, a subunit of the IL-35 receptor, in cancer cells to help them respond to IL-35 during metastasis. Neutralization of IL-35 or knockout of IL-35 in macrophages reduces metastatic colonization. These results indicate the distinct TMEs of primary and metastatic tumors and provide potential targets for intercepting metastasis. Tumor microenvironment varies between primary and metastatic sites. Here they report tumor-associated macrophages from metastatic sites to be predominantly M2 type, and secrete IL-35 to promote metastasis through activation of JAK2–STAT6–GATA3 signaling.